Establishing of a Slovenian open access infrastructure: a technical point of view. Issue 4 (27th August 2014) - Ojsteršek, Milan; Brezovnik, Janez; Kotar, Mojca; Ferme, Marko; Hrovat, Goran; Bregant, Albin; Borovič, Mladen
Abstract : Purpose: – The purpose of this paper is to present a technical perspective when implementing the Slovenian open access infrastructure that consists of four institutional repositories (IRs) and a national portal (NP) that aggregates content from the repositories in order to provide a common search engine, recommendations of similar documents, and similar text detection. Design/methodology/approach: – During the project, the necessary legal background and processes for mandatory submissions of final study works, research publications and research data were established, as well as processes for data exchange between the IRs and the NP, and processes for similar text detection. Findings: – The consortium consisted of four Slovenian universities that significantly differ in size, organisation, and workflows. It was anticipated that exactly the same legal background and software would be used for the four repositories. It turned out that complete unification was impossible due to the differences. Practical implications: – The national open access infrastructure will improve the visibility of Slovenian research organisations. It supports the compliance with the funders' open access mandates. The established infrastructure enables the depositing and archiving of approximately 80 percent of the peer-reviewed scientific publications that are annually published by Slovenian researchers. At the same time, the majority of final study works from Slovenian higher education institutions are available in full-text format. Originality/value: – This paper describes a technical perspective for setting up a national open access infrastructure, which has not been described in the literature previously.